Structural stability study of draw-bar for high-speed maglev trains based on the nonlinear analysis method - LIANG Xin; GUO Feng; RAN Lingkun; YU Dalian; LIU Jianxin (机车电传动)
It is imperative to optimize the structure and improve the reliability and stability in the force transmission process of draw-bar for the application on the high speed maglev trains in the 600 km/h operation. Taking the draw-bar used on the 600 km/h high-speed maglev trains as the research object, this paper explored the impacts of lightweight materials and machining errors on their structural stability with the critical bucking load as the index, according to the stability analysis principle, using the Euler’s formula, the eigenvalue buckling analysis method and the finite element method, and in consideration of the material nonlinear factors and machining errors, and accordingly reveals the influence of the lightweight design of the draw-bar on their structural stability. The relevant conclusions were drawn from the simulative analysis as the following. The mechanical properties of materials have a significant effect on the critical bucking load of the draw-bar, and the critical bucking load of the traditional draw-bar made of 42CrMo alloy steel is triple that of the draw-bar made of 6082 aluminum alloy. Machining errors also affect the structural stability, and the critical bucking load decreases from 40.46 kN to 35.45 kN (down 12.4%) for the draw-bar made of 6082 aluminum alloy subject to a machining error of 3 mm. Therefore, the machining precision should be strictly controlled in the design stage; the non-linear buckling analysis method is more suitable for structural stability analysis of the lightweight draw-bar.